Heavy metals trigger distinct molecular transformations in microplastic-versus natural-derived dissolved organic matter - Xianbao Zhong; Kaiying Zhao; Mengyuan Wu; Yaohui Zhang; Chiyue Ma; Hexiang Liu; Bokun Chang; Xiaohui Lian; Yujing Li; Zixuan Huang; Lang Zhu; Ming Zhang; et al. (Environmental Science and Ecotechnology)
Dissolved organic matter (DOM) is a key determinant of heavy metal fate in aquatic environments, influencing their mobility, toxicity, and bioavailability. Derived from natural sources such as soil and vegetation decomposition, natural DOM (N-DOM) typically features humic-like substances with abundant oxygen-containing functional groups that stabilize heavy metals through complexation. However, microplastic-derived DOM (MP-DOM), increasingly prevalent due to plastic degradation, may interact differently with heavy metals, potentially exacerbating environmental risks amid rising plastic pollution. Yet, how heavy metals drive molecular transformations in MP-DOM versus N-DOM remains unclear, hindering accurate pollution assessments. Here, we compare interactions between N-DOM and MP-DOM with cadmium, chromium (Cr), copper, and lead from both fluorescence and molecular perspectives. Our results show that N-DOM, dominated by humic-like substances (46.0–57.3 %), lignin-like (55.0–64.9 %), and tannin-like (10.1–17.6 %) compounds, forms more stable heavy metal complexes via carboxyl, phenolic hydroxyl, and ether groups than MP-DOM. By contrast, MP-DOM—enriched in protein/phenolic-like substances (13.8–24.0 %), condensed aromatic (12.1–28.5 %), and protein/aliphatic-like (8.6–12.4 %) compounds—yields less stable complexes and is highly susceptible to Cr-induced oxidation. Mass-difference network analysis and density functional theory calculations further reveal that both DOM types undergo heavy-metal-triggered decarboxylation and dealkylation, but N-DOM retains complex structures, whereas MP-DOM degrades into smaller, hazardous molecules such as phenol and benzene. This study underscores the potential for heavy metals to exacerbate the ecological risks associated with the transformation of MP-DOM, providing crucial insights to inform global risk assessment and management strategies in contaminated waters where plastic and metal pollution co-occur.